Natural variation in Caenorhabditis elegans responses to the anthelmintic emodepside - Wit, Janneke (Int J Parasitol Drugs Drug Resist, 2021)
Treatment of parasitic nematode infections depends primarily on the use of anthelmintics. However, this drug arsenal is limited, and resistance against most anthelmintics is widespread. Emodepside is a new anthelmintic drug effective against gastrointestinal and filarial nematodes. Nematodes that are resistant to other anthelmintic drug classes are susceptible to emodepside, indicating that the emodepside mode of action is distinct from previous anthelmintics. The laboratory-adapted Caenorhabditis elegans strain N2 is sensitive to emodepside, and genetic selection and in vitro experiments implicated slo-1, a large K(+) conductance (BK) channel gene, in emodepside mode of action. In an effort to understand how natural populations will respond to emodepside, we measured brood sizes and developmental rates of wild C. elegans strains after exposure to the drug and found natural variation across the species. Some of the observed variation in C. elegans emodepside responses correlates with amino acid substitutions in slo-1, but genetic mechanisms other than slo-1 coding variants likely underlie emodepside resistance in wild C. elegans strains. Additionally, the assayed strains have higher offspring production in low concentrations of emodepside (a hormetic effect). We find that natural variation affects emodepside sensitivity, supporting the suitability of C. elegans as a model system to study emodepside responses across natural nematode populations.